YILDIRIM, İsmail; Cumhuriyet Döneminde Demiryolları (1923-1950), Atatürk Araştırma Merkezi Yayınları, Ankara, 2001, XII+220 Sayfa, ISBN:975-16-1477-5* - Haykır, Yavuz (My University, 2014)
-
Keywords: Tarih